Psychometric evaluation of the endometriosis impact questionnaire (EIQ) in an Iranian population - Mojgan Mirghafourvand; Vahid Ghavami; Maryam Moradi; Khadijeh Mirzaii Najmabadi; Sanaz Mollazadeh (BMC, 2024)
Abstract Background Endometriosis is a benign and chronic gynecological estrogen-dependent disease. Considering the prevalence and the importance of measuring the long-term effects of endometriosis in affected women's lives t the EIQ scale was designed and psychometrically analyzed in English in Australia, in three recall periods (last 12 months, 1 to 5 years ago and more than 5 years ago). It has never been used in Iran and its validity and reliability have not been assessed either. Therefore, the present study aimed to translate and investigate the psychometric properties of the EIQ. Methods In this study, 200 women were selected through random sampling in 2022. After forward and backward translation, the face validity, content validity, and construct validity of EIQ (through Corrected Item-Total Correlation) were examined. To assess the reliability of the scale, both internal consistency (Cronbach's alpha) and test-retest stability methods were employed. Results Impact Score with a score above 1.5 was approved. CVI and CVR values of the EIQ tool were 0.97 and 0.94, respectively. The Item to total Correlation confirmed the construct validity of all seven dimensions of the tool, more than the cut-off (0.3) except lifestyle. Cronbach's alpha coefficient and Intra Correlation Coefficient (ICC) were acceptable for all dimensions. Conclusion The Persian version of EIQ is a valid and reliable scale. This tool is valid and reliable for investigating the long-term impact of endometriosis in Iranian society.